El sistema familiar y su influencia en la conducta del adolescente de bachillerato del colegio “técnico cumandá” provincia de chimborazo, periodo 2009- 2010. - Mogollón, Gabriela (2010)
This research work has as main objective to determine how the family system influences in adolescent behavior, through an investigative guide. The research is based on Systemic Family Therapy, using the inductive-deductive method is a descriptive-explanatory, with design of transverse type field. For data collection surveys and interviews were applied targeting high school students, parents and teachers of the College "Technical Cumandá" of the province of Chimborazo period 2009 - 2010, with a population of 274 people. The research results indicate that 70% of teenagers prefer to spend away from home and share with the family, increasing consumption habits of alcohol and drug snuff.